Genetic deletion of Cyp4f18 disrupts the omega‐3 epoxidation pathway and results in psoriasis‐like dermatitis. Issue 12 (14th November 2022) - Yoshida, Mio; Ishihara, Tomoaki; Isobe, Yosuke; Arita, Makoto
Abstract: Cyp4f18 catalyzes the conversion of n‐3 polyunsaturated fatty acids (PUFAs) into omega‐3 epoxides, such as 17, 18‐epoxyeicosatetraenoic acid (17, 18‐EpETE) and 19, 20‐epoxydocosapentaenoic acid (19, 20‐EpDPE) from eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), respectively. Cyp4f18 ‐deficient mice spontaneously develop psoriasis‐like dermatitis. A significant increase in the number of IL‐17A‐positive gamma delta (γδ) T cells in the skin and enlargement of draining lymph nodes was observed. These symptoms were drastically suppressed by antibiotic treatment. Cyp4f18 is highly expressed in dendritic cells (DCs), and Cyp4f18‐deficient bone marrow‐derived dendritic cells (BMDCs) show markedly increased expression levels of cytokines such as IL‐23 and IL‐1β in response to lipopolysaccharide (LPS) stimulation. Lipidomic analysis of lymph nodes and BMDCs revealed a significant decrease in a series of omega‐3 epoxidized metabolites. Among them, 17, 18‐dihydroxyeicosatetraenoic acid (17, 18‐diHETE), a vicinal diol derived from EPA omega‐3 epoxidation suppressed IL‐23 production in LPS‐stimulated BMDCs in Cyp4f18‐deficient mice. These results demonstrate that Cyp4f18 endogenously produces omega‐3‐epoxidized metabolites in the draining lymph nodes, and these metabolites contribute to skin homeostasis by suppressing the excessive activation of the IL‐23/IL‐17 axis initiated by DCs.